Impact of the Wireless Network’s PHY Security and Reliability on Demand-Side Management Cost in the Smart Grid - El Shafie, Ahmed (2018)
We investigate the impact of the wireless network's physical layer (PHY) security and reliability on demand-side management operation in the smart grid. We assume that consumers communicate their energy demands with the utility, and we investigate the tradeoff between the wireless network's PHY security and reliability. We consider passive and active attacks on the smart grid, and show their impacts on both the wireless communications system's reliability and security. To improve the wireless communications system's security, we propose an artificial-noise (AN)-aided scheme for orthogonal-division multiplexing-based wireless systems. We show that increasing the PHY security of the legitimate transmissions decreases the communication reliability between the smart meters and the meter data-management system since to secure the transmissions, a portion of the transmit powers will be assigned to AN signal transmissions. To further secure the smart meters' transmissions and enhance their reliability, we propose a new encoding scheme where the data are encoded over the available smart meters' communication (i.e., non-idle) times in a given hour.